The Clinical Relevance of Antifibrillarin (anti‐U3‐RNP) Autoantibodies in Systemic Sclerosis. (January 2017) - Tall, F.; Dechomet, M.; Riviere, S.; Cottin, V.; Ballot, E.; Tiev, K. P.; Montin, R.; Morin, C.; Chantran, Y.; Grange, C.; Jullien, D.; Ninet, J.; et al.
Abstract: Systemic sclerosis (SSc) is a heterogeneous autoimmune disease associated with several antinuclear autoantibodies useful to diagnosis and prognosis. The aim of the present multicentric study was to determine the clinical relevance of antifibrillarin autoantibodies (AFA) in patients with SSc. The clinical features of 37 patients with SSc positive for AFA (AFA+) and 139 SSc patients without AFA (AFA−) were collected retrospectively from medical records to enable a comparison between AFA− and AFA+ patients. Antifibrillarin autoantibodies were screened by an indirect immunofluorescence technique using HEp2 cells and identified by an in‐house Western blot technique and/or an EliA test. Comparing AFA+ and AFA− patients, AFA+ patients were significantly younger at disease onset (36.9 versus 42.9; P = 0.02), more frequently male ( P = 0.02) and of Afro‐Caribbean descent (65% versus 7.7%; P < 0.001). At diagnosis, the Rodnan skin score evaluating the cutaneous manifestations was higher (13.3 versus 8.7; P = 0.01) and myositis was also more common in the AFA+ group (31.4% versus 12.2%; P < 0.01). Patients with AFA+ were not associated with diffuse cutaneous SSc or with lung involvement and no difference in survival was observed. Antifibrillarin autoantibodies are associated with patients of Afro‐Caribbean origin and can identify patients with SSc who are younger at disease onset and display a higher prevalence of myositis.